Smartphone Addiction in Turkish Adolescents: A Network Analysis - Kaya, Bilal (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: In this study, the relationship between smartphone addiction nodes was examined by network analysis. The participants consisted of 406 adolescents aged between 13 and 18. Data were collected using the Smartphone Addiction Scale-Short Version. Network analysis was carried out in three steps, which included estimation of the research model, analysis of the network model, and assessment of the stability of network parameters. Among the nodes of the smartphone addiction scale, smartphone addiction 2 and smartphone addiction 7 were determined as the central node, as they had a high degree, betweenness, closeness, and expected influence value. Smartphone addiction 5, smartphone addiction 4, and smartphone addiction 9 had a medium degree, closeness, and expected influence values. The central nodes obtained were found to play an important role in the prevention and intervention programs for adolescents’ smartphone addictions.